Tools with the power to bridge Africa’s climate financing gap - Chilambe, Pedro (2024)
Most of Africa’s one billion people work in agriculture, and small-scale farming is a crucial source of both food and employment; government-implemented climate financing tools could help farmers throughout the continent.